DIAGNOSTIC TEST OF POSTERIOR SEGMENT OCULAR EXAMINATION ON THE SEVERITY OF PEDIATRIC ACUTE LYMPHOBLASTIC LEUKEMIA (ALL) AT DR. MOHAMMAD HOESIN GENERAL HOSPITAL PALEMBANG - Theodorus; Putra, Chani Sinaro; Amin, Ramzi; Sari, Dian Puspita (Majalah Oftalmologi Indonesia, 2023)
Background: Acute lymphoblastic leukemia (ALL) is one of the highest incidence of all cancers in children. Ocular involvement can diagnose the development of the disease. Patients with ALL often have ocular manifestations either resulting from direct infiltration or indirect causes of neoplastic cells. The aim of this study to diagnose from posterior segment findings on disease severity in pediatric patients with acute lymphoblastic leukemia (ALL) at Muhammad Hoesin Hospital Palembang Methods: A diagnostic test to determine the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of posterior segment findings in disease severity diagnostic of pediatric patients with ALL from November 2021 to May 2022. Posterior segment findings that were evaluated included retinal hemorrhages, roth spots, exudate and papilledema. Disease severity of pediatric ALL is divided into high risk and standard risk. All data were analyzed using SPPS version 22.0 Results: There were 68 patients who selected by inclusion criteria. A total of 30 (44.1%) subjects with high risk and 38 (55.9%) with standard risk. in this study there is no patient have papilledema and only one patient (1.5%) has retinal hemorrhage, roth spot and exudate. From statistical analysis, it was found that the three posterior findings had a sensitivity of 0% and a specificity of 97.4%. Conclusion: The results of this study show that the findings of the posterior eye segment can be used as a screening tool for the severity of acute lymphoblastic leukemia, because only one component of sensitivity and specificity has a value of > 80%.